IN SITU RUMEN DEGRADATION KINETICS AND IN VITRO GAS PRODUCTION OF SEED, WHOLE PLANT AND STOVER OF CHENOPODIUM QUINOA - M. Barros-Rodríguez; Cajas-Naranjo M; Núñez-Torres O; Mera-Andrade R; Artieda-Rojas J; Sandoval-Castro C; Solorio-Sánchez J (Journal of Animal and Plant Sciences, 2018)
The nutritional content, in situ rumen degradation of seeds, whole plant and stover of Chenopodium quinoa, as well as, their effect on in vitro gas production and rumen protozoa were evaluated. Six bulls (male castrated) with 412.3 ± 35.23 kg average body weight and fitted with rumen cannula were used. Treatments were: seeds (SEQ), whole plant (WPQ) and stover (SQ) of C. quinoa. The SEQ showed higher CP and gross energy (P <0.05) content and lower fiber content than WPQ and SQ. Rumen degradation (97% DM, 89% CP and 80% NDF) and in vitro digestibility of DM and CP (80 and 88% respectively) were higher for SEQ (P <0.05) than WPQ and SQ. In vitro gas production was 98 ml/0.5 mg fermented DM lower in SEQ and WPQ than SQ (P = 0.0001). However fermentation rate was higher for SEQ and WPQ. The protozoa count was lower in SEQ (P = 0.0001). Seeds of C. quinoa and whole quinoa plant can be incorporated into the diet of ruminants because their good chemical composition, reduced protozoa and high rumen digestion.
Keywords: quinoa; rumen degradation; in vitro gas production